2019
DOI: 10.3390/s19132900
|View full text |Cite
|
Sign up to set email alerts
|

Gas Leakage Source Detection for Li-Ion Batteries by Distributed Sensor Array

Abstract: Lithium-based batteries operation is related to some safety risks of dangerous flaming, integrity destruction, or even explosion. Gas leakage is an early and reliable indicator for such irreversible malfunctioning of electrical accumulators. Often, accurate gas emission source location sensing is difficult especially in heavy operational conditions, related to temperature changes, vibrations, movements, accelerations, etc. In this paper we propose a gas detection system, with catalytic type sensor array, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…(d) Schematic illustration of the battery management system. Panels c and d reproduced with permission from ref . Copyright 2019 The Authors under Creative Commons International Attribution 4.0 License, published by Multidisciplinary Digital Publishing Institute.…”
Section: Gas Sensor Suitable For the Detection And Early Warning Of T...mentioning
confidence: 99%
See 2 more Smart Citations
“…(d) Schematic illustration of the battery management system. Panels c and d reproduced with permission from ref . Copyright 2019 The Authors under Creative Commons International Attribution 4.0 License, published by Multidisciplinary Digital Publishing Institute.…”
Section: Gas Sensor Suitable For the Detection And Early Warning Of T...mentioning
confidence: 99%
“…Notably, “Thermal resistance”, “Stability”, and “Convenience” are marked red because they are special indicators for a gas sensor to detect the battery thermal runaway. Data from refs , , , , and .…”
Section: Gas Sensor Suitable For the Detection And Early Warning Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the worst cases, batteries cause thermal runaway (at about 700 °C) with VOCs, CO, and CO 2 produced [57,58]. Mateev et al [59] pointed out that the presence of CO is related to an incomplete combustion of the electrolyte and to the initial temperature rising, while the presence CO 2 is associated with intensive oxidative processes. Cell thermal runaway showed that a gas detection method targeting CO 2 concentration reacts faster, if compared to temperature monitoring [60].…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…Sedighfar and Moniri [20] also developed an online method for the estimation of the SOC and the SOH of valve-regulated lead-acid (VRLA) batteries, which are oriented toward electric vehicle application. According to Marrero et al [21], the integration of sensors and the development and optimization of a battery management system have great importance in the creation of battery systems in order to increase life expectancy or availability, rather than focusing only on Li-ion batteries, as the majority of researchers are doing; see also [22,23].…”
Section: Introductionmentioning
confidence: 99%